2021
DOI: 10.1016/j.dcn.2021.100978
|View full text |Cite
|
Sign up to set email alerts
|

Neural activation to loss and reward among alcohol naive adolescents who later initiate alcohol use

Abstract: Adolescent alcohol use is associated with adverse psychosocial outcomes, including an increased risk of alcohol use disorder in adulthood. It is therefore important to identify risk factors of alcohol initiation in adolescence. Research to date has shown that altered neural activation to reward is associated with alcohol use in adolescence; however, few studies have focused on neural activation to loss and alcohol use. The current study examined neural activation to loss and reward among 64 alcohol naive 12−14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Consistent with prior research, the present study found that longer response times and poorer accuracy to loss rather than reward stimuli were observed, suggesting that loss processing may have more complex cognitive components ( Sozinov et al, 2020 ). Meanwhile, similar to another study ( Goncalves et al, 2021 ), the present study observed that emotional responses under loss rather than reward anticipation appeared to be associated with SMAs in adolescents. Speculatively, this may reflect imbalanced development of reward/loss sensitivity in early adolescents ( Feldmann et al, 2021 ), such that the loss anticipation modulates broader insula connections than the reward anticipation and thus is more closely associated with future motivated behaviors ( Cho et al, 2013 , Leong et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with prior research, the present study found that longer response times and poorer accuracy to loss rather than reward stimuli were observed, suggesting that loss processing may have more complex cognitive components ( Sozinov et al, 2020 ). Meanwhile, similar to another study ( Goncalves et al, 2021 ), the present study observed that emotional responses under loss rather than reward anticipation appeared to be associated with SMAs in adolescents. Speculatively, this may reflect imbalanced development of reward/loss sensitivity in early adolescents ( Feldmann et al, 2021 ), such that the loss anticipation modulates broader insula connections than the reward anticipation and thus is more closely associated with future motivated behaviors ( Cho et al, 2013 , Leong et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the MID task was used in this study to explore neural activations of reward/loss processing associated with SMAs. Specifically, SMAs-related neural activations in brain regions implicated in both reward/loss processing and emotional regulation, such as the dorsal striatum (DS), ventral striatum (VS), insula, and dorsolateral prefrontal cortex (DLPFC) were extracted ( Chaarani et al, 2021 , Goncalves et al, 2021 , Yee et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, lower activation in these regions might reflect a defining feature of SUD whereby brain activation to aversive outcomes may also promote initiating or prolonging substance use. For instance, adolescents who initiated substance use (versus those abstaining) exhibited changes in striatal activation losses (but not gains) three years later ( Goncalves et al, 2021 ). Evidence also shows striatal responses to aversive stimuli function may direct behavior in alleviating negative outcomes ( Budygin et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, initially alcohol‐naïve adolescents were tested with fMRI during a reward task and were followed for 3 years to determine whether or not they initiated alcohol drinking. Compared with adolescents who did not initiate alcohol use, those who did displayed increased baseline fMRI activation to loss in the left dorsal striatum (putamen) and right precuneus 376 . Finally, a study used connectome‐based predictive modeling with leave‐one‐out cross‐validation to uncover stress‐linked connectivity patterns that differentiated risky from non‐risky drinkers, finding that the stress‐linked network profiles of the risky drinkers predicted loss of control of drinking in the entire sample 377 .…”
Section: Biomarkers In Substance Use Disordersmentioning
confidence: 97%